“We didn’t want to totally break the law”: Industrial Legality, the Pepsi Strike, and Workers’ Collective Rights in Canada - Smith, Charles W. (Labour / Le Travail, 2014)
Canada’s system of industrial legality has routinely limited the collective abilities of workers to strike. Under the conditions of neoliberal globalization, those limitations have intensified. Yet, in 1997, the Retail, Wholesale and Department Store Union (rwdsu) in Saskatoon, Saskatchewan, waged a successful strike against Pepsi-Cola Canada. In addition to defeating the company, the union also expanded workers’ collective rights through a successful constitutional challenge to restrictive common-law rules limiting secondary picketing. This paper examines the history of that strike, exploring the multifaceted strategies that the workers undertook to challenge the company, the state, and the existing law. It argues that workers were successful because they utilized tactics of civil disobedience to defend their abilities to picket. Recognizing that success, the paper is also critical of the Supreme Court of Canada’s decision and its evolution of common-law torts to limit workers’ collective action. The paper concludes by arguing that the Pepsi conflict highlights the importance of civil disobedience in building workers’ movements while emphasizing the inherent limitations of constitutional challenges to further workers’ collective freedoms in Canada.